Effect Of Liquid Smoke on The Morphology and Compatibility of Sago Fiber-Matrix - Muslimin, Mukhlis (Prosiding SEMNAS INOTEK (Seminar Nasional Inovasi Teknologi), 2022)
The study aims to identify the effect of liquid smoke treatment on the surface morphology of sago fibers and its influence on epoxy matrix bonds. The proposed study is divided into two steps: fiber treatments and property tests. In the first treatment, sago fiber is immersed in the liquid smoke solution for 1, 2, 3, 4, and 5 hours, then dried inside an oven at 43 oC for 1 hour. Next, surface morphology and fiber compatibility to the epoxy matrix is observed by Vega3 Tescan Scanning Electron Microscope (SEM). Findings indicate the hat surface morphology of sago fiber with no treatment is relatively smooth, while those with immersion treatments became rough and grooved along with crystallization on the fiber surfaces. The crystallization index is increased throughout increasing immersion durations; leaving more grooves on fiber surfaces which are enhanced the binding quality of sago fiber to the epoxy matrix.